If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + 9) = -24 Reorder the terms: 4(9 + x) = -24 (9 * 4 + x * 4) = -24 (36 + 4x) = -24 Solving 36 + 4x = -24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-36' to each side of the equation. 36 + -36 + 4x = -24 + -36 Combine like terms: 36 + -36 = 0 0 + 4x = -24 + -36 4x = -24 + -36 Combine like terms: -24 + -36 = -60 4x = -60 Divide each side by '4'. x = -15 Simplifying x = -15
| 0.5x+6=0.75 | | -30=9/-5 | | 2-2n=3n+10 | | 4d-3=d+42 | | 5(N+1)=-2n+4(n-4) | | X-7+20=7x-10 | | -2/5÷-2/3 | | (3z+7)(3z+7)= | | 3x=.5(5x+12) | | y+5=-5x | | x^2+31=24 | | D+(1.1+-5d)=4.8 | | 12(5-x)=8 | | (2m-3)=20-4m | | 6(b-5)=18-2b | | 18a+3=3-18a | | 3m-n=-2n | | 5x+17=4x-29 | | -3(c-4)=9 | | 2x8-20/4-8= | | 2x+15=8x-45 | | -16x^2+55x=26 | | 2=20-2(q+P) | | (25+2x)(20+2x)=0 | | 3x^2+30x+75+14(x+5)-5=0 | | 7x+2-4x=46 | | 2x+4=9x-24 | | -24+6=4n | | 6x+7-3y=1 | | 2d+5c=5 | | 4x-y=74 | | -0.4(x-4)=-2 |